WALISONGO: MENGISLAMKAN TANAH JAWA (SUATU KAJIAN PUSTAKA) - Dewi Evi Anita (Kopertais Wilayah X Jawa Tengah, 2014)
AbstractThe majority of Indonesian Islamic . In Javanese society, Walisongo designation is a very well known name and has a special meaning, which is used to refer to the names of the characters are seen as the beginning of broadcasting Islam in Java. The role of the mayor is very big on the course of administration of the empire, especially the Sultanate of Demak. Method development and broadcasting of Islam which is taken for the Mayor prioritizes wisdom. Closing the rulers and the people directly to show the goodness of Islam, giving examples of noble character in everyday life as well as adjusting the conditions and situation of the local community, so it is not the slightest impression of Islam was developed by the Mayor with violence and coercion. Stories of the Guardians is not taken for granted, but the stories of the Guardians of the charismatic deliberately created to elevate the trustees.Keyword: Role Walisongo, method development and broadcasting of Islam, Charismatic Walisongo.